Performance Bottlenecks in a Materials Recovery Facility for Selective Waste Collection - Bianca Ruiz Ferro; Ricardo Gabbay de Souza (Ambiente & Sociedade)
Abstract The efficiency in material recovery at Materials Recovery Facilities (MRF) depends on factors such as the diversity and quantity of waste, adopted processes and technologies, and working conditions. This study aims to analyse the performance bottlenecks of the operational processes at the SC of selective collection in São José dos Campos (SP). The methodology involved primary data collection and analysis, adopting Lean Manufacturing principles to identify process wastage. The SC receives approximately 70 tons/day of waste from selective collection, of which 72.5% are recyclable, but over 40% have been designated as rejects. The waste of materials represented a financial loss of over R$ 2 million in 2018. There is a significant waste of time, especially for exchanging reject containers (approximately 1 hour). Another waste is the number of bags that remain closed throughout the process and are discarded as rejects.